Unveiling nonischemic cardiomyopathies with cardiac magnetic resonance. (February 2014) - Aggarwal, Niti R; Peterson, Tyler J; Young, Phillip M; Araoz, Philip A; Glockner, James; Mankad, Sunil V; Williamson, Eric E
Abstract : Cardiomyopathy is defined as a heterogeneous group of myocardial disorders with mechanical or electrical dysfunction. Identification of the etiology is important for accurate diagnosis, treatment and prognosis, but continues to be challenging. The ability of cardiac MRI to non-invasively obtain 3D-images of unparalleled resolution without radiation exposure and to provide tissue characterization gives it a distinct advantage over any other diagnostic tool used for evaluation of cardiomyopathies. Cardiac MRI can accurately visualize cardiac morphology and function and also help identify myocardial edema, infiltration and fibrosis. It has emerged as an important diagnostic and prognostic tool in tertiary care centers for work up of patients with non-ischemic cardiomyopathies. This review covers the role of cardiac MRI in evaluation of nonischemic cardiomyopathies, particularly in the context of other diagnostic and prognostic imaging modalities.